Ethics and the Archaeology of Violence - González-Ruibal, Alfredo (Springer, 2015)
This volume examines the distinctive and highly problematic ethical questions surrounding conflict archaeology. By bringing together sophisticated analyses and pertinent case studies from around the world it aims to address the problems facing archaeologists working in areas of violent conflict, past and present. Of all the contentious issues within archaeology and heritage, the study of conflict and work within conflict zones are undoubtedly the most highly charged and hotly debated, both within and outside the discipline. Ranging across the conflict zones of the world past and present, this book attempts to raise the level of these often fractious debates by locating them within ethical frameworks. The issues and debates in this book range across a range of ethical models, including deontological, teleological and virtue ethics. The chapters address real-world ethical conundrums that confront archaeologists in a diversity of countries, including Israel/Palestine, Iran, Uruguay, Argentina, Rwanda, Germany and Spain. They all have in common recent, traumatic experiences of war and dictatorship. The chapters provide carefully argued, thought-provoking analyses and examples that will be of real practical use to archaeologists in formulating and addressing ethical dilemmas in a confident and constructive manner.